2003
DOI: 10.1136/vr.153.7.197
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the welfare of dairy caftle using animal‐based measurements: direct observations and investigation of farm records

Abstract: A protocol was developed by consultation with experts on the welfare of cattle to use direct observations of cattle and an examination of farm records to assess welfare. Fifty-three dairy farms in England were visited and assessed during the winter of 2000/01. The findings were compiled and the results of the welfare measurements were examined by 50 experts who indicated at what level they considered that improvement was required. More than 75 per cent of them considered that 32 of the 53 farms needed to take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
319
6
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(359 citation statements)
references
References 15 publications
21
319
6
13
Order By: Relevance
“…The dirtiness of the three body regions demonstrated in this study is mainly caused by disregarding of the recommendations for daily cleaning and bedding change in the barns, but also by the improper stall length. For dairy cows, lameness represents a severe welfare problem decreasing mobility and impairing normal behaviour (Whay et al, 2003). The lameness prevalence in our study was higher in loose housing than in the tie-stalls, but the difference was not statistically significant (P>0.05).…”
Section: Resultscontrasting
confidence: 71%
“…The dirtiness of the three body regions demonstrated in this study is mainly caused by disregarding of the recommendations for daily cleaning and bedding change in the barns, but also by the improper stall length. For dairy cows, lameness represents a severe welfare problem decreasing mobility and impairing normal behaviour (Whay et al, 2003). The lameness prevalence in our study was higher in loose housing than in the tie-stalls, but the difference was not statistically significant (P>0.05).…”
Section: Resultscontrasting
confidence: 71%
“…This reflects the greater effort in farmer recording since the study of Kadarmideen et al (2000), which was also based on UK farmer-recorded data, with mastitis and lameness incidences of 6% and 4%, respectively, across five lactations. Higher incidence rates have been reported in UK literature on mastitis (38.2%) and lameness incidence (23.3%) (Whitaker et al, 2004) and it is commonly reported that incidences based on farmer-recorded health events are lower than veterinary recorded events (Whay et al, 2003). Lameness is less recorded than mastitis, which is reflected by the current dataset.…”
Section: Discussionmentioning
confidence: 47%
“…In addition, science cannot tell us what is socially acceptable or not -and so threshold values are usually set according to expert opinion (e.g. disease prevalence values above which welfare is considered to be poor and where remedial measures are required at herd level can be set from veterinary advice) (Whay et al, 2003a). Finally, ethical, economical and political issues may also come into play (Commission for the European Communities, 2002).…”
Section: Discussionmentioning
confidence: 99%